2020
DOI: 10.1038/s41598-020-67522-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection and identification of a novel bone-targeting peptide for biomedical imaging of bone

Abstract: The global burden of bone-related diseases is increasing in the aging society; thus, improved bone targeted imaging for their early identification and treatment are needed. In this study, we screened novel peptide ligands for hydroxyapatite, a major inorganic component of teeth and bones, and identified a peptide enabling in vivo bone targeting and real-time fluorescence bone detection. To isolate peptides highly specific for hydroxyapatite, we used negative and positive selection from a randomized 8-mer pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…have also discussed the role of noncollagenous proteins enriched with acidic and phosphorylated amino acid in regulating the nucleation and growth of HAp for bone mineralization. Bang et al have compared the HAp binding affinities of a set of peptides with positive (basic amino acids) and negative charge (acidic amino acids) and illustrated that the positively charged peptides (KNFQSRSH) exhibited better binding with HAp . Gungormus et al also reported the ionic interaction of positively charged, histidine-binding peptides with phosphates of HAp .…”
Section: Resultsmentioning
confidence: 99%
“…have also discussed the role of noncollagenous proteins enriched with acidic and phosphorylated amino acid in regulating the nucleation and growth of HAp for bone mineralization. Bang et al have compared the HAp binding affinities of a set of peptides with positive (basic amino acids) and negative charge (acidic amino acids) and illustrated that the positively charged peptides (KNFQSRSH) exhibited better binding with HAp . Gungormus et al also reported the ionic interaction of positively charged, histidine-binding peptides with phosphates of HAp .…”
Section: Resultsmentioning
confidence: 99%
“…As revealed using the fourth Garnier–Osguthorpe–Robson algorithm (GOR4), out of the entire AP-2 family, AP-2δ has the largest number of extended strands but the smallest of random coils ( Figure 2 E). Bang et al suggested that binding affinity could be elevated with the increase of extended strands in secondary structure [ 38 ]. Particular attention was also given to the amino acids preceding the conserved “TF_AP-2” domain; these were evaluated for their similarity, physicochemical properties, and structural characteristics ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In another example, Bang et al identified a supposedly highly specific HA-binding peptide via phage display and combined it with the fluorescent Cy5.5 dye. 180 During in vivo real-time wholebody imaging, the conjugate showed preferential binding for bone tissues. The development of probes for nuclear imaging was also attempted, but with unsatisfactory results.…”
Section: Biomedical Applications Of Solid-binding Peptidesmentioning
confidence: 99%